Neighbourhood satisfaction and QOUL in middle-income housing in Kuala Lumpur city, Malaysia - Mohit, Mohammad Abdul; Ali, Mohamed Sajid (Malaysian Institute of Planners, 2016)
This paper is based on the subjective perception of the residents about the neighbourhood environment and their quality of urban life. The neighbourhood satisfaction provides a generalized view into the well-being of the residents, and it has been viewed as a significant aspect of the quality of urban life (QOUL). As a contributor to life satisfaction, neighbourhood satisfaction is influenced by individual and household socio-economic variables, along with the neighbourhood characteristics. However, there is limited understanding of how neighbourhood environments influence neighbourhood satisfaction and the quality of urban life. This paper intends to examine the relationship between residents’ neighbourhood satisfaction and their quality of urban life in a middle-income housing area in Kuala Lumpur City, Malaysia, by using 100 sample respondents that fulfilled a confidence level of 90% of the population. The findings of the study indicate that the residents are satisfied with their existing QOUL, but if no actions are taken it will deteriorate. Therefore, several recommendations are made for improving the residents’ QOUL.